Demonstration of Code-Mixing in Kasih Aba-Aba by Naykilla, Tenxi, and Jemsii - Maulidana, Diva; Rusmawaty, Desy; Sucahyo, Didik; Hermagustiana, Istanti; Setiawan, Iwan (English Education Department at FKIP Nommensen University, 2025)
This study aims to examine the phenomenon of code-mixing in the Indonesian pop song 'Kasih Aba-aba' by Naykila, Tenxi, and Jemsii, with a focus on the structural types and linguistic purposes of code-mixing in the lyrics. Employing a qualitative descriptive method and a content analysis approach, this research utilized a purposive sampling strategy to select this specific song as a rich case study due to its prevalent use of English-Indonesian code-mixing and its popularity on digital platforms. Line-by-line analysis of the lyrics was part of the research process, and each instance of code-mixing was categorized using Muysken's (2000) typology of insertion, alternation, and congruent lexicalization and its functions were interpreted using sociolinguistic frameworks (Gumperz, 1982; Hoffman, 1991; Poplack, 1980). Findings indicate that insertion is the most common kind of code mixing, followed by alternation and congruent lexicalization. These are employed to accomplish a variety of sociolinguistic goals, including emphasis, identity expression, prestige, and emotional personalization. English elements used for stylistic purposes represent global influence, young identity, and multilingual proficiency. The purposeful use of Bahasa Indonesia and English enhances the emotional tone of the lyrics and aligns with current linguistic trends in Indonesian youth culture. The results indicate that code-mixing in popular music acts as both a communicative and cultural strategy. This research adds to our knowledge of bilingual language usage in media discourse and has practical implications for discourse-based English training and the development of culturally relevant language curricula. The limitation of the study is that study only focuses on a single song, which limits generalizability. Therefore, future research is recommended to expand into cross-artist comparisons and to investigate audience reception.